Biological risk among agriculture and construction workers in Molise Region, Central Italy - Tamburro, Manuela; Anzelmo, Vincenza; Bianco, Paolo; Sammarco, Michela Lucia; Salierno, Francesco; Ripabelli, Giancarlo (La Medicina del Lavoro, 2017)
Background: Biological risk is a significant issue in workplaces due to continuous modification of work organization and condition. Objectives: In this pilot study, perception and knowledge of biological risk, as well as adoption of prevention measures were evaluated among construction and agriculture workers. Methods: A structured questionnaire was administered to workers to collect socio-demographic and employment information, in addition to data on risk perception and knowledge, and adoption of preventive measures, including those related to work activities. Results: Fifty-three workers aged 45.3±9.8 years participated in the study, 81% were male, and 70% were construction workers. Approximately 80% of participants declared that infectious diseases are neither frequent nor health-threatening in their occupational activity. The majority of workers considered some diseases, such as hepatitis A and B, leptospirosis and listeriosis, as posing a low risk to their health. Forty-seven % claimed to be unexposed to biohazards at their workplace, and 72% were not worried about them. Ninety-six % of the workers knew about vaccination for tetanus, but only 74% and 36% knew about the availability of vaccination for Hepatitis A and B, respectively. During lifetime, 94% of the workers received at least one vaccination. All workers had undergone tetanus vaccination, but only few received vaccine for influenza, hepatitis B and tuberculosis. Conclusions: This pilot study in occupational settings revealed a poor perception of biological risk and a limited awareness of the severity of infectious diseases. Major knowledge gaps existed about the available preventive measures. It is essential to promote safety culture at the workplace also with regard to biological hazards. This requires improving information and education, conducting appropriate studies, and prompting health and safety professional actors to focus on occupational infectious disease problems.